Entropy of corneal nerve fibers distribution observed by laser scanning confocal microscopy: A noninvasive quantitative method to characterize the corneal innervation in Sjogren's syndrome patients. Issue 12 (24th October 2015) - Bianciardi, Giorgio; Latronico, Maria Eugenia; Traversi, Claudio
ABSTRACT: Sjogren's syndrome (SS) is a progressive autoimmune condition mainly affecting the salivary and lacrimal glands with an incidence of primary SS between 1/100 and 1/1, 000. SS implies an alteration in the epithelium and subepithelium innervation, with consequent reduction of corneal sensitivity. It is necessary to have noninvasive quantitative methods to characterize the status of the corneal nerve fibers of the patients in order to choose and follow the best therapy. Entropy (information dimension) of the nerve corneal fibers distribution observed by confocal microscopy was evaluated in patients with primary SS ( n = 30, 6 males, 24 females, 21–81 years), diagnosed by biopsy of salivary gland and blood tests and in sex‐ age‐matched healthy subjects ( n = 12). Corneal nerve fiber density, Langerhans cell count, and cell density in the nerve plexus images were also evaluated. In selected patients salivary gland atrophy degree was also evaluated. Nerve corneal distribution observed by confocal microscopy is fractal. Entropy of the corneal nerve distribution statistically distinguishes between SS patients and healthy subjects: patients present a lower value of information dimension of the corneal nerve fibers distribution than healthy individuals ( P < 0.001). Percentage of grouped cases classified by entropy according to the subjects (selected patients vs. healthy) showed a 100% sensitivity and 96% specificity, P < 0.0001 with a low value of coefficient of variation among the individuals (6–7 times lower than the other morphometric indexes). Entropy correlated with the severity of the disease (salivary gland atrophy degree, P < 0.01). Evaluation of entropy of the corneal nerve distribution observed by a laser confocal microscopy appears to quantitatively and noninvasively characterize an aspect of the SS patients in relation to the recognition of an impairment of their ocular surface, giving us for the first time a method to objectively and precisely characterize the corneal innervation status in the SS patients. Microsc. Res. Tech. 78:1069–1074, 2015 . © 2015 Wiley Periodicals, Inc.